A survey of helminths and arthropods in stray dogs in Kuala Lumpur - Abdul Rahman, Sheikh Omar; Lee , C. C.; Whitten, L. K. (Persatuan Doktor Veterinar Malaysia, 1985)
Eighty eight stray dogs in Kuala Lumpur were surveyed for helminths and arthropods over a six month period. Eighty five (96.6%) harboured one or more species of parasites of which 60 (75.0%) had both helminths and arthropods, 16 (18.2%) had helminths only and 3 (3.4%) had arthropods only. Eight species of helminths were identified, the common ones being the hookworms - Ancylostoma caninum (91.5%), A. ceylanicum (91.5%) and A. braziliense (78.0%). The burden of infection was heavy with the hookworms and Trichuris vulpis. Eight species of arthropods were identified in 69 dogs, the three most common ones being Rhipicephalus sanguineus (69.6%), Ctenocephalides felis orientis (63.8%) and Heterodoxus spiniger (53.6%). The significance of the findings were discussed.